2022
DOI: 10.1093/plcell/koac153
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the chloroplast inner envelope protein TIC100 impair and repair chloroplast protein import and impact retrograde signaling

Abstract: Chloroplast biogenesis requires synthesis of proteins in the nucleocytoplasm and the chloroplast itself. Nucleus-encoded chloroplast proteins are imported via multiprotein translocons in the organelle’s envelope membranes. Controversy exists around whether a 1 MDa complex comprising TIC20, TIC100 and other proteins constitutes the inner membrane TIC translocon. The Arabidopsis thaliana cue8 virescent mutant is broadly defective in plastid development. We identify CUE8 as TIC100. The tic100cue8 mutant accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Similar tethering and transfer facilitating activities have been observed in other MORN motif‐containing proteins. JPH proteins in muscle and neuronal cells tether the ER to the PM for lipid transfer and calcium dynamics between the ER and the PM (Woo et al, 2016), and TIC100 on the chloroplast inner envelope is critical for chloroplast protein import (Loudya et al, 2022). Because of the low expression of MORN1‐GFP in transgenic plants, all localization studies were carried out by transient expression in Arabidopsis protoplasts and N. benthamiana leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Similar tethering and transfer facilitating activities have been observed in other MORN motif‐containing proteins. JPH proteins in muscle and neuronal cells tether the ER to the PM for lipid transfer and calcium dynamics between the ER and the PM (Woo et al, 2016), and TIC100 on the chloroplast inner envelope is critical for chloroplast protein import (Loudya et al, 2022). Because of the low expression of MORN1‐GFP in transgenic plants, all localization studies were carried out by transient expression in Arabidopsis protoplasts and N. benthamiana leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high levels of import are observed for a subset of proteins when TIC56 or YCF1 are inhibited (Köhler et al, 2015;Bölter and Soll, 2017). Mutant tic100 Arabidopsis plastids import less than one-third of the protein of wild type plants, and the abundance of 1-MDa translocation complex are reduced by more than one-half, however (Loudya et al, 2022). TIC21 is suggested to be an essential translocon component (Teng et al, 2006;Kikuchi et al, 2009), while it has also been characterized an iron transporter and is phylogenetically related to cyanobacterial permeases (Duy et al, 2007); later studies indicated that it does not co-purify with the TOC/TIC translocation complex (Kikuchi et al, 2013;Nakai, 2015a).…”
Section: Tic Channel Componentsmentioning
confidence: 99%
“…Indeed, PhANG expression in gun1 is only higher than that of the lincomycin/norflurazon-treated wild type; it is still much lower than that of the untreated wild type or gun1 mutants. Thus, this model cannot be used to explain the reduced expression of PhANGs in ppi2 , tic100 cue8 , or any other virescent mutants (with import defects) in comparison with the healthy wild type ( Kakizaki et al., 2009 ; Loudya et al., 2022 ). The reduced protein import in the ppi2 or tic100 cue8 mutant represses the biogenesis of chloroplasts, thus triggering downregulation of PhANG expression, further indicating that chloroplasts with disturbed proteostasis emit a retrograde signal to tune nuclear gene expression for rebalancing proteostasis.…”
Section: Retrograde Signaling Related To Chloroplast Proteostasismentioning
confidence: 99%